How does the use of artificial intelligence affect the concept of fair trial? - Heikkinen,Tiia-Helinä (2019)
The purpose of this thesis is to function as a path to further discussion regarding human rights and the use of artificial intelligence (AI) in the court proceedings. Artificial intelligence technology has become a highly relevant topic to many parts of our lives. AI is used and will be used in different ways as a part of the court proceedings; namely, for collecting and sorting out information, suggesting and predicting decisions, in the decision making, and in the appeal process. This thesis introduces four examples of the possible use of AI in the court proceedings. Additionally, the thesis introduces how the AI is currently used in the judiciary, and how it could be used in the judiciary in the future. Example of the use of AI from Finland is also introduced. However, it has been seen that the use of AI is limited to specific tasks and that the use of AI in the court proceedings could affect the elements of fair trial protected in the Article 6 of the European Convention on Human Rights. This thesis attempts to provide an answer to the question: “How does the use of artificial intelligence in the court proceedings affect the elements of fair trial?”. The research is concentrating into the following elements of fair trial: the reasonable time requirement, an independent and impartial tribunal, equality of arms, immediacy, and the right to get reasoned judgement. The thesis highlights the positive and the negative implications for the elements of right to a fair trial, following from the use of AI in the court proceedings. All in all, it seems that there would be more negative implications, than positive implications following from the use of AI in the court proceedings. The use of AI systems in the court proceedings could harm the independency of the judiciary and the impartiality of the process. Imbalances between the parties who have different technological abilities could make the appeal process incredibly hard, and in turn affect the principle of equality of arms. Furthermore, the use of predictive justice systems could cause imbalances between the parties and have negative implications for the principle of the equality of arms. In some cases AI may have to anticipate the judgement for the case if it cannot otherwise effectively do the required research. AI would then be giving guidelines for the judge on how to decide the case, which would mean that judge might base his or her decisions into some other AI generated materials. This would have negative implications for the principle of immediacy. The use of AI in the court proceedings could make the whole reasoning of the decisions complicated to understand, it would lack transparency, and it would not be a sufficient reasoning for a decision. Positive implications are mainly related to the length and cost of the proceedings. The use of AI in the court proceeding speeds up the whole process and improves legal protection and legal certainty. This could in addition save a lot of money. There could be also less mistakes in the proceedings, since AI could eliminate human failures.
Keywords: Human rights; Artificial intelligence; Fair trial; AI